2008
DOI: 10.3892/mmr_00000063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mitochondrial A3243G mutation loads in easily accessible samples from a family with maternally inherited diabetes and deafness

Abstract: Abstract. The mitochondrial A3243G mutation is most commonly related to the MELAS syndrome, but can cause many different clinical manifestations at various ages. Here, we present a family with maternally inherited diabetes and deafness (MIDD), the proband of which exhibits hearing loss, diabetes mellitus, cardiomyopathy and short stature. Four easily accessible samples (whole blood, hair roots, buccal scrapings and urinary sediment) from the proband and her 3 sons were simultaneously analyzed for heteroplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…DNA from urothelium, myocardium, and buccal mucosa had the higher while blood had the lowest proportion of mutant genomes. These results are consistent with a previous research ( 20 ). Each time a somatic cell undergoes mitosis, mtDNA will be randomly distributed to the progeny cells along with mitochondria.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…DNA from urothelium, myocardium, and buccal mucosa had the higher while blood had the lowest proportion of mutant genomes. These results are consistent with a previous research ( 20 ). Each time a somatic cell undergoes mitosis, mtDNA will be randomly distributed to the progeny cells along with mitochondria.…”
Section: Discussionsupporting
confidence: 94%
“…Further, ragged red fibers on muscle biopsy are typically seen in MIDD, which indicate damaged muscles and are thought to be pathognomonic of mitochondrial disease ( 19 ). Muscle biopsy may show ragged-red fibers that are characteristic of mitochondrial disorders and contribute to the diagnosis of MIDD ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] In particular, the well-known m.A3243G mutation in tRNA Leu(UUR) was implicated in the pathogenesis and progression of T2DM in many families worldwide. [9][10][11] This mutation affected the structural stability, aminoacylation rate and post-transcriptional modification of tRNA Leu(UUR) . 12 In addition to the m.A3243G mutation, some case-control studies suggested that tRNA Trp A5514G and tRNA Ser(AGY) C12337T, 13 tRNA Glu A14692G, 14 tRNA Ala T5587C and ND5 T12338C 15 mutations were associated with T2DM.…”
Section: Introductionmentioning
confidence: 99%